An environmental DNA sampling method for aye‐ayes from their feeding traces. Issue 18 (31st July 2018) - Aylward, Megan L.; Sullivan, Alexis P.; Perry, George H.; Johnson, Steig E.; Louis, Edward E.
Abstract: Noninvasive sampling is an important development in population genetic monitoring of wild animals. Particularly, the collection of environmental DNA (eDNA) which can be collected without needing to encounter the target animal facilitates the genetic analysis of endangered species. One method that has been applied to these sample types is target capture and enrichment which overcomes the issue of high proportions of exogenous (nonhost) DNA from these lower quality samples. We tested whether target capture of mitochondrial DNA from sampled feeding traces of the aye‐aye, an endangered lemur species would yield mitochondrial DNA sequences for population genetic monitoring. We sampled gnawed wood where aye‐ayes excavate wood‐boring insect larvae from trees. We designed RNA probes complementary to the aye‐aye's mitochondrial genome and used these to isolate aye‐aye DNA from other nontarget DNA in these samples. We successfully retrieved six near‐complete mitochondrial genomes from two sites within the aye‐aye's geographic range that had not been sampled previously. Our method demonstrates the application of next‐generation molecular techniques to species of conservation concern. This method can likely be applied to alternative foraged remains to sample endangered species other than aye‐ayes. Abstract : We applied target capture to obtain mitochondrial DNA sequences from environmental DNA samples from aye‐aye feeding traces. We retrieved six near‐complete mitogenomes from two previously unsampled sites in the aye‐aye's range. This method can likely be applied to other rare and elusive species of conservation concern.